CD4 Lymphocytopenia without HIV Infection - Insiripong, Somchai; Insiripong, Wattana (Maharat Nakhon Ratchasima Hospital Journal, 2024)
It is well known that the most common cause of the low CD4 (CD4 less than 300/mm3) is the long term HIV infection. Other far less common causes include tuberculous infection, lymphoma, etc. The aim of this report is to describe the low CD4 count in various diseases, except for HIV infection. Patients and Methods: This cross-sectional study recruited the IPD medical patients who had lymphocyte < 1,000/mm3 during 1 Jan-31 Mar 2015. They would be checked for CD4 using the flow cytometry method, BD FACSCalibur® and only ones who had CD4 <250/mm3 without HIV infection, aplastic anemia, myelodysplastic syndrome, leukemia, steroid, chemotherapy or radiotherapy and organ transplantation were collected for demographic and clinical data study and expressed as the percentage, mean and standard deviation. Results: From 14 patients with lymphocyte < 1,000/mm3, only 10 patients had CD4 < 250/mm3, consisting of 8 males and 2 females, their ages ranged from 22 to 85, mean 53.7+23.7 years. Four patients were older than 60 years. Their active diseases were pneumonia with respiratory failure (3 cases), COPD with respiratory failure (2 cases), pulmonary tuberculosis (2 cases), disseminated tuberculosis, adult onset Still’s disease and lepromatous leprosy (1 case for each). The mean for lymphocyte, T cell and CD4 count were 475.3+175.6, 323.9+179.9 and 158.9+62.2/mm3, respectively. Conclusion: Low CD4 count can be occasionally found in various diseases such as severe pneumonia, tuberculosis. It may contribute the patients to be vulnerable to opportunistic and more serious infections.